Diagnostic Issues in Early-Onset Obsessive-Compulsive Disorder and their Treatment Implications - Burchi, Elisabetta; Pallanti, Stefano (Current Neuropharmacology, 2019)
Background: The lifespan approach and recent shift in the conceptualization of Obsessive- Compulsive Disorder (OCD) promoted by the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM5) along with novel insights into the pathogenesis of this heterogeneous disorder are driving the development of new outcome measures and new treatments for a disease that, on the other hand, is characterized by high rates of refractoriness. Objective and Methods: The aim of this review is to provide a discussion of the translational evidence about Early Onset OCD (EO) in compliance with a neurodevelopmental and RdoC perspective. Results and Conclusion: EO might be considered the neurodevelopmental subtype of OCD. Indeed there is evidence that different clusters of symptoms and dimensions at an early stage predict different trajectories in phenotype and that distinct neurocircuit pathways underpin the progression of the disorder. Despite the development of high refractoriness in the course of the disorder, evidence suggests that EO may be particularly treatment responsive in the early stages, thus showing the need for early recognition and additional recovery oriented studies in this subgroup. Consistent with the neurodevelopmental perspective, immunity and glutamate neurotransmission are emerging as novel pathways for parsing out the neurobiology of OCD, the EO form, in particular, supporting the implementation of new multisystemic models of the OCD phenotype. Brain connectivity patterns, immune and microbiome profiles are standing out as promising areas for biomarkers with the potential for targeted personalized therapies in EO.
Keywords: neuroinflammation